Particle production beyond the thermal model - Wolschin, Georg (XLV International Symposium on Multiparticle Dynamics, Wildbad Kreuth, 4-9 Oct 2015, ISMD 2015, 2016)
The sources of particle production in relativistic heavy-ion collisions are investigated from RHIC to LHC energies. Whereas charged-hadron production in the fragmentation sources follows a ln(sNN/s0) law, particle production in the mid-rapidity low-x gluon-gluon source exhibits a much stronger dependence ∝ ln3(sNN/s0), and becomes dominant between RHIC and LHC energies. The equilibration of the three sources is investigated in a relativistic diffusion model (RDM). It agrees with the thermal model only for t → ∞.
Gesehen am 02.09.2020